The The Effect of Leadership and Compensation on Employee Performance with Motivation as Moderating Variables at the Pangeran Hotel Pekanbaru - Lilik Hidayati; Zulher Zulher (LPPM of NAROTAMA UNIVERSITY, 2022)
Purpose: Employees are always required to give good performance to the company where they work, as well as employees at Hotel Prince Pekanbaru. This study aims to analyze the direct and indirect effect of the leadership variable on performance and the direct and indirect influence of the compensation variable on employee performance and the influence of motivation on performance. Design/methodology/approach: Data analysis was carried out using the SEM model using the Smart PLS version 3.00 program. Findings: The results of this study conclude that leadership has a significant effect on performance, leadership is mediated by motivation on performance, compensation has a significant effect on performance and compensation has an indirect effect on performance, and motivation has a significant effect on employee performance at Hotel Pangeran Pekanbaru. Research limitations/implications: The sample used was 87 employees, and the data used were primary and secondary data obtained through questionnaires and research files. Originality/value: This paper is original Paper type: Literature review